Addressing Financial Accountability Challenges in an Indonesian Waqf Institution: Insights post-PSAK 412 Implementation - Alimuddin, Nur Hazimah; Suandi, Aprilia Beta (The Indonesian Journal of Accounting Research, 2025)
This study examines how and to whom financial accountability is practiced and assesses the post-implementation application of PSAK 412 at a pseudonymous waqf institution. We use a qualitative single-case design with semi-structured interviews, observation, and document analysis. Data were analyzed using thematic analysis, with line-by-line in vivo and descriptive coding, followed by focused/axial coding to develop subthemes and categories. Findings show accountability is predominantly upward to leaders. A divine-ownership framing—where endowed assets are viewed as belonging to Allah rather than to waqifs or the institution—reinforces purpose fidelity but narrows formal reporting to human stakeholders. Digital tools strengthen internal routines but, by themselves, do not produce PSAK-consistent, public-facing transparency. Financial statements show selective alignment with PSAK 412, notably in recognition timing and the completeness of Notes/Disclosure. The paper contributes a Dual-Accountability Translation perspective that shifts from a normative ideal to an operable model of how spiritual accountability is rendered into institutional outputs (statements, disclosures, accessible summaries). It concludes that modern governance regimes mediate and materialize Islamic accountability; without enabling conditions, translation remains partial. Limitations include the reliance on internal perspectives, early post-implementation timing, and the inability to observe the full deed-to-certificate process.